Collaborative Governance in the Management of the Bogor Halimun Salak Geopark - Muhammad Jalaludin Assayuti; Rita Rahmawati; Euis Salbiah; Ginung Pratidina; Novel Anak Lydon; Cecep Wahyudin (Universitas Djuanda, 2025)
The Bogor Halimun Salak Geopark is a conservation area that integrates geological richness, biodiversity, and local cultural heritage. Located in Bogor Regency, it serves as a hub for environmental education and preserving Kasepuhan traditions. Despite its potential, the geopark's management encounters complex challenges, particularly in actor collaboration. This study explores the implementation of collaborative governance in geopark management and identifies factors influencing its effectiveness. A descriptive quantitative method was used with a saturated sampling of 58 respondents, consisting of government officials and local community members. Data collection involved interviews, observations, literature review, documentation, and Likert-scale questionnaires. Findings indicate that collaborative governance falls within the